Fund managers' ability in making investment decision: comparative study between Malaysia and USA - Mohamed, Zulkifli; Jaafar, Muhamad Sukor; Ahmad, Ismail (Institut Pengurusan Penyelidikan & Jaringan Industri, 2006)
The Central Bank of Malaysia has encouraged local investors to invest abroad, raising the question of whether foreign markets are beatable. This comparative study examines how fund managers make investment decisions in the Malaysian and United States markets. A sample of 20 unit trust funds was selected from both markets for the period 2002–2005. The funds were appraised in terms of volatility, diversification, fund ranking, performance consistency, and forecasting ability regarding market timing and stock selection. The study found that Malaysian unit trust returns are more volatile than United States funds, a trend mirrored by the respective stock markets. All funds were found to be under-diversified and demonstrated inconsistent performance over time. Fund rankings using the Sharpe and Treynor indices showed that 80% of United States unit trusts outperformed the market, compared to only 40% in Malaysia. Furthermore, fund managers' forecasting ability, measured by the Jensen Alpha index, indicated that 90% of United States fund managers were able to make correct forecasts, compared to 40% of Malaysian managers. Therefore, it can be deduced that it is easier for United States fund managers to outperform their market. Consequently, it is recommended that fund managers and investors invest abroad, as evidence suggests that foreign markets are more beatable despite potential inconsistency.